Peningkatan Pengetahuan dan Pemanfaatan Waste Cooking Oil sebagai Sabun Padat dengan Essential Oil Lemon (Increasing Knowledge and Utilization of Waste Cooking Oil as Solid Soap with Lemon Essential Oil) - Soliha, Annisa Mayang; Widianingrum, Aulivia; Hidayat, Irvan; Kusuma, Rizki Perdana (Persatuan Dosen Kesehatan Masyarakat, 2026)
Used cooking oil waste generated from household activities has the potential to pollute the environment if not managed properly, but it can be utilized to produce useful and economically valuable products. This study aims to analyze the increase in community knowledge after providing educational materials and training on processing waste cooking oil into solid soap with the addition of lemon essential oil. The method used was pre-experimental with a one group pretest-posttest design on 30 respondents in Pesawahan Village, Teluk Betung. The level of knowledge was measured before and after the intervention, then analyzed using the N-Gain Test. The results showed an increase in the average knowledge score from 45 on the pretest to 92.61 on the posttest, with a normalized average increase of 0.83, which is classified as high. A total of 86.67% of respondents experienced an increase in knowledge in the high category. It can be concluded that education and training on processing used cooking oil into solid soap with lemon essential oil is effective in increasing public knowledge and has the potential to encourage more environmentally friendly and sustainable household waste management.Keywords : waste cooking oil, community education, knowledge improvement, solid soap, essential oil lemon